The Impact of Health Information System on Medical and Pharmaceutical Decision-Making in Government Hospitals: A Cross-Sectional Study in Saudi Arabia - Mana Ali Alsulaiman; Mohammed Ahmed Alshehri; Naif Nasser Alotaibi; Abdulrahman Mohammad Al Ghamdi; Adel Ali Almaashy; Fouad Burayd Alzahrani; Ali Hadi Al Dughman; Nada Dhafer Al Mukhalas; Munahia Mohammed Mubarak Alyami; Hassan Shajea Al Rezg (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Health information systems are essential for obtaining the data needed to make medical and pharmaceutical decisions to improve healthcare outcomes. Therefore, the study aimed to investigate the impact of health information systems on medical and pharmaceutical decision-making in government hospitals in Saudi Arabia. Methods: A cross-sectional study was conducted among 368 healthcare workers (HCWs) including Medical Informatics, physicians, pharmacists, and administrators from August 2024 to October 2024. Study participants were selected using simple random sampling techniques. Descriptive statistics mean and percentage were calculated. The study used a generalized linear mixed model. Variables with a p-value < 0.05 were considered as predictors of HIS use. Results: The results showed a statistically significant positive relationship between the effectiveness of health information systems and the efficiency of decision-making, as these systems contributed to improving the accuracy and reliability of the available data. The R² value was 0.259, indicating that 26% of the variance in decision-making can be explained by health information systems. Conclusion: The study emphasizes the need to strengthen training and resources allocated to these systems to ensure better health outcomes, which enhances the effectiveness of health care delivery.